Attentional Processing in C57BL/6J Mice Exposed to Developmental Vitamin D Deficiency - Harms, Lauren R. (Public Library of Science, 2012)
Epidemiological evidence suggests that Developmental Vitamin D (DVD) deficiency is associated with an increased risk of schizophrenia. DVD deficiency in mice is associated with altered behaviour, however there has been no detailed investigation of cognitive behaviours in DVD-deficient mice. The aim of this study was to determine the effect of DVD deficiency on a range of cognitive tasks assessing attentional processing in C57BL/6J mice. DVD deficiency was established by feeding female C57BL/6J mice a vitamin D-deficient diet from four weeks of age. After six weeks on the diet, vitamin D-deficient and control females were mated with vitamin D-normal males and upon birth of the pups, all dams were returned to a diet containing vitamin D. The adult offspring were tested on a range of cognitive behavioural tests, including the five-choice serial reaction task (5C-SRT) and five-choice continuous performance test (5C-CPT), as well as latent inhibition using a fear conditioning paradigm. DVD deficiency was not associated with altered attentional performance on the 5C-SRT. In the 5C-CPT DVD-deficient male mice exhibited an impairment in inhibiting repetitive responses by making more perseverative responses, with no changes in premature or false alarm responding. DVD deficiency did not affect the acquisition or retention of cued fear conditioning, nor did it affect the expression of latent inhibition using a fear conditioning paradigm. DVD-deficient mice exhibited no major impairments in any of the cognitive domains tested. However, impairments in perseverative responding in DVD-deficient mice may indicate that these animals have specific alterations in systems governing compulsive or reward-seeking behaviour.